Scabies: Treatment, Complication, and Prognosis - Reqgi First Trasia (PT Kalbe Farma Tbk., 2021)
Scabies is a skin infestation caused by Sarcoptes scabiei mite. In 2017, WHO included scabies in the list of neglected tropical diseases.Treatment of scabies is currently still problematic due to late diagnosis and not adequately managed complications. Skabies adalah penyakit kulit yang disebabkan oleh tungau Sarcoptes scabiei. Pada tahun 2017, WHO menggolongkan skabies dalam daftar penyakit tropis yang terabaikan. Pengobatan skabies saat ini masih bermasalah karena keterlambatan diagnosis. Komplikasinya pun tidak ditangani dengan baik.